Legal Approaches to Data Transfer and Traceability in CRM Value Chains Internationally - Naeem AllahRakha; Umida Shaakbarovna Sharaxmetova; Burxanova Leyla Mariusovna; Abdullayeva Malikabonu Erkin Kizi; Akramov Akmaljon Anvarjon Ugli (Contrarius Indonesia, 2026)
China controls nearly 90% of the global supply of strategic rare earth elements, and its 2025 export restrictions exposed significant vulnerabilities in global critical raw material (CRM) supply chains. Although many jurisdictions have adopted traceability requirements to improve supply chain transparency, these measures increasingly conflict with national data sovereignty regulations, creating a legal trilemma involving transparency, data control, and international trade. This study examines the legal implications of divergent data sovereignty regimes for CRM traceability and evaluates the adequacy of existing international mechanisms governing cross-border data transfers. The research employs a normative legal method using statutory, conceptual, comparative, and analytical approaches to assess the compatibility of domestic regulatory frameworks with international trade obligations. The findings reveal three principal conclusions. First, existing international and domestic legal frameworks governing cross-border data transfers remain fragmented, generating regulatory inconsistencies that undermine the effectiveness, reliability, and interoperability of CRM traceability systems. Second, an effective international traceability framework requires harmonized legal standards that establish clear and proportionate rules, recognize the legal validity of digital traceability records, safeguard legitimate state interests in strategic data governance, and facilitate secure cross-border information exchange. Third, although the traceability trilemma cannot be completely resolved because transparency, data sovereignty, and international trade embody competing legal priorities, a balanced international legal framework aligned with World Trade Organization principles can reduce regulatory conflicts, strengthen legal certainty, prevent disguised trade restrictions, and promote trustworthy cooperation throughout the global CRM value chain.